2023
DOI: 10.3390/ijms24065668
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Prenatal Exposure to Methamphetamine on the Development of Dopaminergic Neurons in the Ventral Midbrain

Abstract: Methamphetamine, a highly addictive central nervous system (CNS) stimulant, is used worldwide as an anorexiant and attention enhancer. Methamphetamine use during pregnancy, even at therapeutic doses, may harm fetal development. Here, we examined whether exposure to methamphetamine affects the morphogenesis and diversity of ventral midbrain dopaminergic neurons (VMDNs). The effects of methamphetamine on morphogenesis, viability, the release of mediator chemicals (such as ATP), and the expression of genes involv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…The claimed prevalence rates of substance misuse in Islamic nations are influenced by various factors. [ 10 11 12 13 14 ]…”
Section: Discussionmentioning
confidence: 99%
“…The claimed prevalence rates of substance misuse in Islamic nations are influenced by various factors. [ 10 11 12 13 14 ]…”
Section: Discussionmentioning
confidence: 99%
“…Recent data suggest that methamphetamine use during pregnancy impairs differentiation of the ventral midbrain dopaminergic neurons by altering the expression of relevant genes involved in neurogenesis [36]. Moreover, recent studies demonstrated that H3K9me2mediated silencing is an important epigenetic regulator of gene expression throughout development [28], while a reduction in H3K9me2 levels and downregulation of G9A, a specific lysine 9 methyltransferase (K9MT), has been observed in the brain of mice repeatedly exposed to cocaine [37].…”
Section: Discussionmentioning
confidence: 99%